Castle in the sky [videorecording (Blu-Ray + DVD)] - Miyazaki, Hayao, 1941-; Hisaishi, Jō, 1950-; Kanada, Yoshinori (Shout Factory, 2017)
Pazu is an engineer's apprentice who finds Sheeta, a young girl, floating down from the sky, wearing a glowing pendant. Together, they discover both are searching for Laputa, a legendary floating castle, and vow to unravel the mystery of the luminous crystal around Sheeta's neck. Their quest won't be easy. There are greedy air pirates, secret government agents and astounding obstacles to keep them from learning the truth.